Combination of IFN-gamma with STING agonist and PD-1 immune checkpoint blockade: a potential immunotherapy for gastric cancer - Hosseinzadeh, Shahnaz; Imani, Mahsa; Pourfarzi, Farhad; Jafari, Narjes; AbedianKenari, Saeid; Safarzadeh, Elham (Medical oncology (Northwood, London, England), 2024)
Suppression of the cGAS-STING pathway is an immune escape mechanism in cancer cells. The critical role of this pathway in gastric cancer (GC) is not fully understood. Herein, we evaluated the effect of the interferon-gamma (IFN-gamma), STING agonist, PD-1 immune checkpoint blockade, and their combination on the cGAS-STING pathway in GC. Expression of cGAS and STING in tumor tissue samples and adjacent normal tissue (ANT) biopsies of fifty new GC patients was evaluated by quantitative real-time PCR (qRT-PCR). Moreover, cGAS and STING expression levels were examined in Peripheral Blood Mononuclear Cells (PBMC) samples of forty GC patients and twenty-five healthy subjects. The apoptosis rate of cancer cells was analyzed by Annexin V-FITC/PI. Cell proliferation was measured by the BrdU assay. Also, IFN-β levels were evaluated in the supernatants of the treated groups. The cGAS expression was decreased in patients with distant metastasis. Co-cultures treated with IFN-gamma showed an elevated level of cGAS and STING expressions in PBMC and cancer cells. The rate of apoptosis increased in all the treatment groups. In addition, the rate of proliferation in PBMCs increased in different treated groups. The main role of PBMCs in cytotoxicity was determined by a comparative analysis of the viability of cells treated with all treatments, both with and without PBMCs. The production of IFN-β was elevated in all treated groups. The current study suggests that a combination therapy using IFN-gamma, STING agonist, and anti-PD-1 antibody can provide a promising approach to the treatment of GC.